(untitled) (Práxis Educativa, 2018)
This work analyzes the learning of teaching from the insertion of teachers in initial formation in school every day. It seeks to understand how the learning for teaching is built from processes of homology of the practice, seen as a condition for producing reflections on the knowledge of teacher learning that are achieved in the daily life of the school from the relationship between teacher in professional practice and in-service teachers. The study involved two graduates of the course of Letters of the State University of Bahia, participants of the Institutional Program of Initiatives for Teaching - PIBID. As a research device, we use narrative interviews in the conception of the (auto) biographical approach. The study pointed out that teaching learning is built, also in the daily life of the school, in which educational practices are taken as an element of reflection for the construction of a proper way of conceiving teaching. Keywords: PIBID. Routine of the school. Learning of the teaching.